"Modelliing,, Estiimatiion and CFAR Detectiion in non-Gaussiian Cllutter Modélisation, Estimation et Détection CFAR dans un Milieu de Clutter non-Gaussien" - Gouri, Amel (Université M'sila, 2020)
Compound Gaussian (CG) models with different texture components have been utilized to describe sea clutter statistics at low grazing angles. In the first work, the well-known K, Pareto type II and compound Gaussian inverse Gaussian (CGIG) models are combined firstly to produce mixture distributions with thermal noise. Using Intelligent Pixel Processing (IPIX) real data, the fitting of the proposed models are investigated where a simplex algorithm based on the Nelder-Mead algorithm is used to achieve the unknown parameters from the data. Regardless of heavy computation time, fitting results to empirical data showed the efficiency of the proposed mixtures models against the standard distributions in several cases. The second work considered in this thesis is the development of new estimation procedures labeled higher order moments estimator (HOME), constrained non-integer order moments estimator (CNIOME) and constrained maximum likelihood estimation (CMLE) for parameter estimation of CGIC clutter plus noise. The HOME method is given in a closed-form for both known and unknown clutter-to-noise ratio (CNR). As the last two estimators are given in integral forms, the Gauss quadrature method based on Legendre and Laguerre polynomials is used after splitting the underlying integrals into two parts. Using simulated and real data, estimation performances of the proposed methods are assessed in terms of known and unknown clutter to noise ratio. In the case of known CNR, it is shown that the HOME and the CMLE methods can produce similar estimates of the shape parameter at high sample sizes. For unknown CNR, both CNIOME and CMLE methods present approximate results. Moreover, the HOME exhibits poor estimation results for all values of the shape parameter. When the number of integrated pulses and CNR values are high, the CMLE method outperforms always the CNIOME and the HOME methods. In radar target detection, parametric and non-parametric Constant False Alarm Rate (CFAR) detectors for Weibull distributed clutter have been suggested achieving the full CFAR property. The performances of these CFAR algorithms are measured by CFAR loss in homogeneous and heterogeneous environments. The improvement of detection performances in terms of low time-consuming which is very important in real time applications is also considered. To this effect, the zlog(z) based estimator for CFAR detection in homogeneous Weibull clutter is used. This estimation method is obtained in terms of the digamma function where the estimates of the shape parameter are determined by the interpolation tool. The non-integer order moments estimator (NIOME) is also given and coincides the zlog(z) estimation results for low values of the moment’s fractional order. Based on the Neyman-Pearson type test, CFAR detection comparisons, based on the proposed estimator and the existing logt-CFAR and maximum likelihood CFAR (ML-CFAR) detectors, are conducted. Résumé Les modèles Gaussiens composés construits par diverses composantes de texture ont été utilisés pour représenter les statistiques du clutter de mer à faibles angles d’incidence. Dans ce cas, les modèles connus sous les noms K, Pareto type II et CGIG sont combinés pour former des distributions mélangées. En supposant la présence du bruit thermique, l’approximation des modèles proposés est examinée à l’aide des données réelles IPIX où l’algorithme de Nelder-Mead est utilisé pour obtenir les paramètres inconnus. Cette procédure d’estimation possède un temps de calcul important et l'ajustement des résultats aux données empiriques a montré l'efficacité des modèles composés proposés par rapport aux distributions standards dans la plupart des cas. Le deuxième travail considéré dans cette thèse est le développement de nouvelles procédures d'estimation, à savoir HOME, CNIOME et CMLE, pour l'estimation des paramètres du clutter CGIC plus bruit. Pour un CNR connu et inconnu, l’expression compacte de la méthode HOME a été trouvée. Comme les deux derniers estimateurs sont présentés sous forme d’intégrales, la méthode de Gauss quadratique basée sur les polynômes de Legendre et Laguerre est utilisée après la division des intégrales en deux parties. A partir des données réelles et simulées, les performances d’estimation des méthodes proposées sont évaluées en termes du CNR. Dans le cas du CNR connu, il a été montré que les méthodes HOME et CMLE peuvent produire des estimés du paramètre de forme similaires pour un nombre d’échantillons élevé. Pour un CNR inconnu, les méthodes CNIOME et CMLE présentent des résultats approximatifs. La méthode HOME présente de mauvais résultats pour toutes les valeurs du paramètre de forme. Lorsque le nombre d'impulsions et le CNR sont élevés, la méthode CMLE offre de meilleurs résultats par rapport aux autres approches. Les détecteurs paramétriques et non paramétriques CFAR ont été utilisés pour un clutter de distribution de Weibull. Les performances de ces algorithmes CFAR sont mesurées par la perte CFAR dans des environnements homogènes et hétérogènes. L'amélioration des performances de détection en termes de faible consommation de temps qui est très importante dans les applications en temps réel est également envisagée. À cet effet, l'estimateur basé sur la statistique zlog (z) pour la détection CFAR dans le cas du clutter Weibull homogène est utilisé. Cette méthode d'estimation est obtenue en fonction de la fonction digamma où les estimations du paramètre de forme sont déterminées par l'outil d'interpolation. L'estimateur NIOME est également donné et coïncide avec les résultats d'estimation zlog (z) pour les faibles valeurs de l'ordre fractionnaire du moment. A l’aide du test de Neyman-Pearson, des comparaisons de détection CFAR basées sur l'estimateur proposé et les détecteurs logt-CFAR et ML-CFAR existants ont été effectuées. في هذا العمل. تم استخدام نماذج غاوسي المركبة التي أنشئت بواسطة مكونات نسيج مختلفة لتمثيل زاوية حدوث فوضى البحر المنخفضة , يتم دمج النماذج المعروفة باسم GIGϹ و Κ و pareto لتكوين توزيعات مختلطة. بافتراض وجود ضوضاء حرارية ، يتم فحص تقريبي للنماذج المقترحة باستخدام بيانات IPIX الحقيقية التي يتم من خلالها استخدام خوارزمية نيلدر ميد للحصول على المعلمات غير المعروفة. يحتوي إجراء التقدير هذا على وقت حساب طويل، وقد أظهر ملائمة النتائج للبيانات التجريبية فعالية النماذج المركبة المقترحة مقارنة بالتوزيعات القياسية في معظم الحالات. العمل الثاني الذي أنجز في هذه الأطروحة هو تطوير إجراءات تقدير جديدة ، وهي HOME و CMLE و CNIOME . لتقدير فوضى GIGϹ بالإضافة إلى معلمات الضوضاء. بالنسبة ل CNR معروف وغير معروف ، تم استخدام طريقة HOME نظرًا لأنه يتم تقديم المقدرين الأخيرين كتكامل، يتم استخدام طريقة غوس التربيعية على أساس متعدد الحدود Laguerre و Legendre بعد تقسيم التكاملات إلى جزأين. من البيانات الحقيقية والمحاكاة ، يتم تقييم أداء التقدير للطرق المقترحة من حيث CNR . في حالة CNR معروف، فقد تبين أن طرق HOME و CMLE يمكن أن تنتج تقديرات معلمة الشكل مماثلة لعدد كبير من العينات) M (. بالنسبة ل CNR غير معروف, تقدم أساليب CMLE و CNIOME نتائج تقريبية. تعرض طريقة HOME نتائج سيئة لجميع قيم معلمة الشكل. عندما يكون عدد النبضات و CNR مرتفع، تقدم طريقة CMLE نتائج أفضل مقارنة بالنهج الأخرى تم استخدام كاشفات CFAR حدودي وغير حدودي لفوضى توزيع ويبل. يتم قياس أداء خوارزميات CFAR هذه في البيئات المتجانسة وغير المتجانسة. تحسين أداء الكشف من حيث استهلاك الوقت المنخفض هو أمر مهم جدًا في تطبيقات الوقت الفعلي. لهذا الغرض ، يتم استخدام المقدر بناءً على إحصاء )z( ZLoɡ لاكتشاف CFAR في حالة فوضى ويبل، يتم الحصول على طريقة التقدير هذه كدالة لوظيفة diɡamma. مقدر لحظة الترتيب غير الصحيح، يتم أيضًا تقديمه ويتزامن مع نتائج التقدير )z( ZLoɡ للقيم المنخفضة للترتيب الكسر للحظة. باستخدام اختبار نيمان بيرسون، تم إجراء مقارنات للكشف عن CFAR بناءً على المقدر المقترح وكاشفات LoɡtCFAR و MLCFAR الحالية